Effect of drying methods on yield, physicochemical properties, and total polyphenol content of chamomile extract powder - Sin Yee Lee; Vincent Ferdinand; Lee Fong Siow (Frontiers in Pharmacology, 2022)
Chamomile (Matricaria chamomilla L.) is a traditional medicinal plant used to treat hay fever, inflammation, muscle spasms, menstrual disorders, insomnia ulcers, wounds, gastrointestinal disorders, rheumatic pain, and hemorrhoids. Dried chamomile flowers have a longer shelf life and the dried extract in form of powder offers much flexibility for new therapeutic formulations as it could be used as a replacement for liquid extract and serve as a shelf-stable ingredient in new applications. This study aims to determine the effect of drying methods, i.e., convection oven-drying at 45 °C, freeze-drying at −50°C, and spray-drying at 140°C at 10.5 and 12 ml/min, respectively) on powder yield, physicochemical properties (moisture content, water activity, and color attributes), and total polyphenol content of chamomile extract powder. Our findings showed that spray-drying conducted at 140°C, 12 ml/min resulted in the lowest yield of powder (16.67%) compared to convection oven-drying (90.17%) and freeze-drying (83.24%). Decreasing the feed flow rate to 10.5 ml/min during spraying caused an increase in powder yield to 26.99%. The moisture content of spray-dried chamomile extract powder obtained at 140°C, 10.5 ml/min was higher (11.00%) compared to that of convection oven-dried (8.50%) and freeze-dried (7.50%). Both convection oven-dried and freeze-dried chamomile extract powder displayed no significant difference (p > 0.05) in moisture content. The higher feed flow rate (12 ml/min) in spray-drying also led to an increase in the moisture content of chamomile extract powder to 12.00%. The higher residual moisture found in the spray-dried samples resulted in partial agglomeration of particles. In terms of water activity, freeze-dried chamomile extract powder was found to have the highest water activity (0.63) compared to that of convection oven-dried (0.52), spray-dried at 140°C, 10.5 ml/min (0.57), and spray-dried at 140°C, 12 ml/min (0.58). Spray-dried and freeze-dried chamomile extract powder with high moisture content and water activity could be highly susceptible to microbial growth. In terms of color attributes, higher drying temperature in spray-drying led to darker, redder, and more yellowish chamomile extract powder that could be caused by heat-induced Maillard reaction and caramelization. Since lower drying temperature was used in both convection oven-drying and freeze-drying, both convection oven-dried (56.94 mg GAE/g powder) and freeze-dried chamomile extract powder (55.98 mg GAE/g powder) were found to have higher total polyphenol content compared to those of spray-dried (42.79–46.79 mg GAE/g powder). The present findings allow us to understand the effect of drying methods on the properties of chamomile extract powder and provide a better drying option to dry chamomile extract. Due to higher powder yield with ideal powder properties such as low moisture content and water activity, desirable color, and high total polyphenol content obtained from convection oven-drying, convection oven-drying was a better option than freeze-drying and spray-drying for drying chamomile extract.